HUBUNGAN KEMAMPUAN KETERAMPILAN DASAR MENGAJAR MAHASISWA PROGRAM PENGALAMAN LAPANGAN (PPL) JURUSAN TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA TERHADAP HASIL BELAJAR SISWA DI SMK PADA BIDANG KEAHLIAN TEKNIK BANGUNAN GEDUNG - Yudhi Tri Pratama; Tuti Iriani; Amos Neolaka (Jurnal Pensil : Pendidikan Teknik Sipil, 2012)
This research aims to determine the relationship between student’s basic skill of teaching during Teaching Apprenticeship Program (PPL) at the Department of Civil Engineering Faculty of Engineering – State University of Jakarta and the results of learning process at vocational school majoring in building engineering. The research was conducted in nine vocational schools majoring in building engineering in the second semester – school year 2011/2012. The method used is surveying with the correlation approach, student’s basic skill of teaching data obtained from 240 samples PPL using Likert questionnaire that had been tested its model of validity and reliability. Validation is done by analyzing each item of proble; while reliability is obtained by using a formula that produces alpha r of 0.971 with the interpretation criteria is very high. Preparation of hypothesis testing is using regression done by generating a regression equation Y = 37.493 + 0.238 x. Hypothesis testing is done by t test and obtained tcount> Ttable with α = 0.05 (8.65> 1.651). Further, testing of correlation coefficient (rxy) with Product Moment formula obtained rxy = 0.489, the value shows the pattern of relationships was quite variable. The result of calculation of the coefficient of determination (rxy2) is 0.239. This means that the students' vocational 23.90% influenced by teaching students the basic skills of PPL. Thus the study concluded there is a relationship between teaching students the basic skills of the Field Experience Program (PPL) Department of Civil Engineering Faculty of Engineering, State University of Jakarta on vocational students' basic skills in the areas of teaching expertise